Perancangan Ilustrasi Tata Cara Penggunaan Kendaraan Umum sebagai Media Edukasi - Edo Galasro Limbong; Ismail Bambang Subianto; Friza Youlinda Parwis; Prin Suprianto (Universitas Indraprasta PGRI Jakarta, 2019)
Procedure is a process that is often overlooked by someone because it is considered not too important, there are no strict rules, no clear education, and so on. The procedure itself is closely related to manners because of matters regarding actions or actions. Basically doing procedures can have an impact on the people around them. One of them is the procedure for using public vehicles for angkot cars and MRT trains. Education on the procedures for use needs to be done starting from adolescence. So the purpose of this study is to design an illustrative media for how to use public vehicles as an educational medium. This research uses qualitative research methods with the approach taken is the creative process of creating works. The data collection technique of this research is by field observations, interviews, and literature studies. Thus, the results of this study are illustrations of procedures for public vehicle use of angkot cars and MRT trains that can be used as a medium of information and education for teenagers.